Fiscal and legal monitoring of judicial consideration of cases of customs offenses - Gerchakivsky, Sviatoslav; Gerchakivska, Olha (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The features of legal support of counteraction to customs offenses in Ukraine are investigated, fiscal and legal aspects of detecting offenses in the customs sphere are tracked, the consequences of consideration of protocols on violation of customs rules by customs, the application of administrative penalties by courts are analyzed. The practice of the European court on the rights of the people is characterized in part of the information about the law-enforcing meetings in Ukraine.